Efficacy and Safety of Long-Pulsed Nd-Yag Laser in Treatment of Hirsutism - Rosie, Tawhida Nawazesh; Khan, Md Abdul Latif; Khan, Md Shirazul Islam; Yazdi, Quazi Salim; Karim, ATM Rezaul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Hirsutism is a condition of unwanted malepattern hair growth in women. Perception of hirsutism is subjective and it is a common condition affecting 5-10% of unselected women. Objectives: To find out the efficacy and safety of long-pulsed Nd-YAG laser in the treatment of hirsutism. Materials and Methods: Fifty females of age between 18- 50 years with dark terminal facial hair and normal hormonal profile were treated with long-pulsed Nd-YAG laser (1064nm, 10mm spot size, pulse duration of 25-30 minutes and fluence of 25-40J/cm2). Six consecutive sessions of laser treatment were delivered to all the patients at 4 to 6 weeks’ interval. Photographic evaluations and percentage of hair reduction were done before each session and final assessment noted at the end ofninemonths. Results: All the patients completed the study. Good hair reduction (50-75%) was seen in 52% of patients after the first treatment session. After six consecutive treatment sessions at the end of nine-month excellent hair reduction (>75%) was noted in 86% of patients and good hair reduction (50-75%) seen in 12% patients. Side effects in our study were post-operative erythema in 40% and perifollicular oedema in 33.33%. Conclusion: The study supportslong-pulsed Nd-YAG laser with multiple six sessionsis safe and effective in the treatment of hirsutism. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 169-172